Agricultural Personnel Diversity Management Scale: Design, reliability and validity - Gámez Gámez, Karina; López Torres, Virginia Guadalupe (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The world of work is characterized by the diversity (racial and ethnic, gender, generational and age, religious and spiritual, disability, socioeconomic and sexual orientation) of people that converge in it, a characteristic that represents a management opportunity to create effective teams, recognizing that diversity can generate competitive advantages. Considering this reality, the objective is to develop a questionnaire to measure diversity management based on an empirical model designed with the variables internal management of cultural diversity, tolerance to diversity, equality and respect, labour equity, integration, selection, intercultural communication and communication.